Peptide chemistry and drug design - Dunn, Ben M. (Hoboken, New Jersey : Wiley, 2015)
"This book details many of the problems and successes of peptides as potential drugs"--Provided by publisher.
Peptide therapeutics -- Methods for the peptide synthesis and analysis -- Peptide design strategies for g-protein coupled receptors (GPCRs) -- Peptide-based inhibitors of enzymes -- Discovery of peptide drugs as enzyme inhibitors and activators -- Discovery of peptide drugs from natural sources -- Modification of peptides to limit metabolism -- Delivery of peptide drugs.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Drugs -- Design; Peptide drugs; Peptides -- Synthesis; Peptides -- chemistry; Drug Design; Pharmaceutical Preparations; MEDICAL -- Pharmacology; Drugs -- Design; Peptide drugs; Peptides -- Synthesis; Electronic books